Africa RISING in Mali – impact brief - Azzarri, Carlo; Boukaka, Sedi Anne; Vitellozzi, Sveva (International Food Policy Research Institute, 2023)
Interventions/Innovations Africa RISING (AR) initiatives in Mali were implemented in Bougouni, Yanfolila, and Koutiala cercles (administrative units) in the Sikasso region of the country. The initiatives included an ambitious cropping systems component focused on the adoption of improved crop varieties (sorghum, groundnut, okra, eggplant, and tomato) and farming methods (cereal-legume intercropping, cereal-vegetable intercropping, and fertilizer microdosing). Livestock system interventions aimed at improving small ruminant production through improved feeding and vaccination, while natural resource management activities concentrated on the reduction of soil erosion through contour bunding. Program interventions also included a series of nutrition-oriented trainings directed to extension workers and women as well as the establishment of nutrition support groups.